Records, information and data exploring the role of record keeping in an information culture - Yeo, Geoffrey (Facet Publishing, 2018)
This dynamic book considers whether and how the management of records (and archives) differs from the management of information (and data). Can archives and records management still make a distinctive contribution in the 21st century, or are they now being dissolved into a wider world of information governance? What should be our conceptual understanding of records in the digital era? What are the practical implications of the information revolution for the work of archivists and records managers? Geoffrey Yeo, a distinguished expert in the global field, explores concepts of ‘records’ and ‘archives’ and sets today’s record-keeping and archival practices in their historical context. He examines changing perceptions of records management and archival work, and asks whether and how far understandings derived from the fields of information management and data administration can enhance our knowledge of how records function. He argues that concepts of information and data cannot provide a fully adequate basis for reflective professional thinking about records and that record-keeping practices still have distinct and important roles to play in contemporary society